Konstitusionalitas Pemerintah Adat Suku Nuaulu - Patiasa Soumory; Jemmy Jefry Pietersz; Victor Juzuf Sedubun (Postgraduate Program in Law, Universitas Pattimura, 2023)
Introduction: Customary government in the constitution provides a space where the constitutional rights of every citizen are guaranteed by the state.Purposes of the Research: This research aims To review and the unity of the Nuaulu tribe as a customary law community according to the 1945 Constitution. And analyze and review The implementation of the customary government system of the Nuaulu tribe is a constitutional right of the Nuaulu tribe.Methods of the Research: The type of research is normative legal research. problem approach in this study is a statutory approach, and a case conceptual approach, legal materials are primary legal materials and secondary legal materials, legal materials that have been collected and grouped using a legal approach, then synchronized with legal concepts and principles studied to be analyzed normatively to answer the legal issues studied rely on the approach that used in this study.Results of the Research: The results of this study It is the constitutionality of the customary government of the nuaulu tribe because constitutional rights already exist and are recognized and regulated in accordance with reality within the scope of the nuaulu